Sub-neutralizing levels of antibodies against RSV F protein enhance RSV infection via Fc-FcγR interactions - Luo, Tingting; Zhao, Xin; Lu, Yi; Tan, Wen; Peng, Bingming; Zhong, Li; Ma, Jinhua; Mei, Chenghao; Bu, Huaqin; Tian, Daiyin (Frontiers in Immunology, 2025)
Respiratory syncytial virus (RSV) is a major cause of severe lower respiratory tract infections in infants, and antibody-dependent enhancement (ADE) presents a significant challenge in vaccine and antibody development. This study investigated the molecular mechanism of ADE mediated by sub-neutralizing antibodies against RSV F protein. We demonstrated that anti-RSV F antibody could facilitate RSV attachment and endocytosis into cells via Fc-Fc gamma receptor (FcγR) interactions while only at sub-neutralizing levels, it increased RSV replication and release, thereby inducing ADE. ADE was abrogated following the secondary occlusion of F protein using nirsevimab Fab fragments. During ADE, intracellular inflammatory signaling pathways were overactivated, resulting in elevated secretion of pro-inflammatory factors (IL-1β, IL-6, TNF-α). FcγRI was identified as the dominant receptor of ADE through blockade experiments, and dual inhibition of FcγRI and TLR4 abolished ADE, highlighting their synergistic role. Furthermore, ADE-induced cytokines upregulated FcγRs expression, creating a self-reinforcing inflammatory loop. Overall, our findings indicated that (1) sub-neutralizing F-specific antibodies increase RSV entry via FcγRs, whereby partially unsealed F protein allows subsequent membrane fusion and enhances replication; (2) RSV ADE pathogenesis involves the coordination of FcγRI and TLR4 signaling pathways, and is amplified by cytokine-driven upregulation of FcγRs. These findings are helpful for the development of next-generation antibody and vaccine against RSV.